The Efficacy of Tetracyclines in Peripheral and Intracerebral Prion Infection - De Luigi, Ada (Public Library of Science, 2008)
We have previously shown that tetracyclines interact with and reverse the protease resistance of pathological prion protein extracted from scrapie-infected animals and patients with all forms of Creutzfeldt-Jakob disease, lowering the prion titre and prolonging survival of cerebrally infected animals. To investigate the effectiveness of these drugs as anti-prion agents Syrian hamsters were inoculated intramuscularly or subcutaneously with 263K scrapie strain at a 10(−4) dilution. Tetracyclines were injected intramuscularly or intraperitoneally at the dose of 10 mg/kg. A single intramuscular dose of doxycycline one hour after infection in the same site of inoculation prolonged median survival by 64%. Intraperitoneal doses of tetracyclines every two days for 40 or 44 days increased survival time by 25% (doxycycline), 32% (tetracycline); and 81% (minocycline) after intramuscular infection, and 35% (doxycycline) after subcutaneous infection. To extend the therapeutic potential of tetracyclines, we investigated the efficacy of direct infusion of tetracyclines in advanced infection. Since intracerebroventricular infusion of tetracycline solutions can cause overt acute toxicity in animals, we entrapped the drugs in liposomes. Animals were inoculated intracerebrally with a 10(−4) dilution of the 263K scrapie strain. A single intracerebroventricular infusion of 25 µg/ 20 µl of doxycycline or minocycline entrapped in liposomes was administered 60 days after inoculation, when 50% of animals showed initial symptoms of the disease. Median survival increased of 8.1% with doxycycline and 10% with minocycline. These data suggest that tetracyclines might have therapeutic potential for humans.